Reading comprehension achievement: A comparative study between science and social science students - Ida Muliawati (Studies in English Language and Education, 2017)
This study was aimed at finding different achievements in reading comprehension between the science and social science students at a senior high school in Banda Aceh. It was also aimed at finding factors that influenced their achievements by using a comparative study involving 40 second grade (year 11) students of the school. The instruments used for this study were a reading comprehension test and a questionnaire searching for answers about language attitude, intelligence and motivation of the students towards the English subject. The result from the t-test was 3.67 which were higher than t-table of 2.042 at the level of significance of 0.05. This indicated that the levels of students’ achievement in reading comprehension in the two programs were quite different. The study also found and discussed the factors that made positive differences in achievement of these two groups of students in reading comprehension; they were positive attitudes toward the language, high motivation and higher intelligence.